2166. Timely Antiviral Therapy for Influenza-Associated Hospitalizations in Pediatric Solid Organ Transplant Recipients in the United States. (15th December 2022) - Amarin, Justin Z; Haddadin, Zaid; Spieker, Andrew J; Godown, Justin; Halasa, Natasha B; Dulek, Daniel
Abstract: Background: Pediatric solid organ transplant (SOT) recipients are at high risk of complications from influenza and those with documented or suspected influenza should receive antivirals as soon as possible. We aimed to compare outcomes between pediatric SOT recipients who did or did not receive timely antiviral therapy for an influenza-associated hospitalization (IAH). Methods: We linked the Pediatric Health Information System (PHIS) and Scientific Registry of Transplant Recipients (SRTR) databases and queried the merged database for single SOT recipients < 18 years old who were transplanted between 1/1/2006 and 6/1/2016 and had at least one IAH within 3 years. We excluded children who contracted influenza or died during the transplant encounter and those who did not have follow-up data. We defined "timely" antiviral therapy as the receipt of antivirals no more than 2 days after hospitalization and compared the outcomes of children who did or did not receive timely antiviral therapy using Pearson's χ 2 test or the two-sample t -test with unequal variances, as appropriate. Results: Of 12, 419 children, 379 (3.1%) had at least one IAH. The most common organ transplant was kidney ( n =133 [35.1%]). Of 270 children (71.2%) who received antivirals, 225 (83.3%) received them within 2 days of hospitalization. Oseltamivir was the most frequently administered influenza-specific antiviral ( n =268 [99.3%]). The outcomes of children who received timely antiviral therapy and those who did not are compared in Table 1 . The proportion of children who received timely antiviral therapy increased over the study period from 33.3% in 2007 to 100% in 2019 (Figure 1 ). Table 1 Outcomes of pediatric SOT recipients who did or did not receive timely antiviral therapy. Figure 1 Proportions of pediatric SOT recipients who did or did not receive timely antiviral therapy. Conclusion: Timely influenza-specific antiviral therapy was associated with better outcomes in pediatric SOT recipients with IAH. Importantly, more than one-third of children did not receive timely antiviral therapy. Further studies are needed to identify and address barriers to timely antiviral therapy. Disclosures: Natasha B. Halasa, MD, Quidel: Grant/Research Support|Quidel: equipment donation|Sanofi: Grant/Research Support|Sanofi: HAI testing and vaccine donation Daniel Dulek, MD, Eurofins/Viracor: Grant/Research Support.